Analysis of the Impact of the SARS-CoV-2 Pandemic on the Stage and Access to Oncology Services in Brazil for the Treatment of Rectal Cancer - Souza, Guilherme da Costa; López, Rossana Verónica Mendoza; Hashizume, Pedro Henrique Shimiti; Lopes, Edia Filomena Di Tullio; Novaes, Hillegonda Maria Dutilh (Brazilian Journal of Oncology, 2025)
Cancer is a major social, public health, and economic challenge worldwide, accounting for 1 in 6 deaths globally, according to Globocan 2022. Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, there has been a noticeable impact on the provision of services to oncology patients. The present study aimed to analyze the effect of the pandemic on access to healthcare services and disease staging at a specialized oncology hospital located in the state of São Paulo.Demographic, clinical, and access data were extracted from 3 electronic information systems, comparing 3 periods: prepandemic (2018–2019), pandemic (2020–2021), and postrestriction easing (2022 to June 2023). The results showed progression in the clinical stage of patients referred to for treatment from the pandemic period onwards. In the prepandemic period, approximately 9.4% of patients presented at clinical stage IV. During the pandemic, this percentage increased to 15.4%, and in the postrestriction easing period, it reached 17.8%.Although access to effective oncological treatment was improved during the pandemic, there was a noticeable progression in the clinical stage of the disease, which persisted after the easing of restrictions.
Keywords: rectal neoplasm; access to health services; COVID-19; staging; neoplasm; acess to health services